PENGARUH KECERDASAN EMOSIONAL, KOMUNIKASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI PADA KANTOR PELAYANAN PUBLIK DI KABUPATEN PURBALINGGA - Romantik Citra Impiansi; Hermin Endratno (Media Ekonomi, 2014)
The study was aimed to find out whether or not the emotional intelligence, communication, and working environment individually have a significant effect to the work performance of the civil servants. The respondents in the study were all the state servants working in three public service offices, including the Office of Integrated Investement and Business Permits, the Vehicle-Tax Payment Office (Samsat), and the Office of Population and Civil Administration. The sampling method was a saturated sampling. The data were analyzed using multiple linear regression. Based on the result of analysis, it could be concluded that the variables of emotional intelligence, and working environment individually have no significant effect to the work performance of the employees. One variable having a significant effect on the work performance among the civil servants is the communication. However, the three variables simultenaously have significant effects to their performance. From the findings, it is suggested that the offices should explore more deeply the emotional intelligence, communication, and the working environment to improve their staffs. Keywords: emotional intelligence, communication, working environment, work performance.